2021
DOI: 10.1186/s12883-021-02352-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of hybrid FDG-PET/MRI on decision-making in presurgical evaluation of drug-resistant epilepsy

Abstract: Background When MRI fails to detect a potentially epileptogenic lesion, the chance of a favorable outcome after epilepsy surgery becomes significantly lower (from 60 to 90% to 20–65%). Hybrid FDG-PET/MRI may provide additional information for identifying the epileptogenic zone. We aimed to investigate the possible effect of the introduction of hybrid FDG-PET/MRI into the algorithm of the decision-making in both lesional and non-lesional drug-resistant epileptic patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
5
1
1
Order By: Relevance
“…Several studies have shown relationships between pathologic classification and operative results undergoing MRI or PET examination with FCD [ 7 , 15 , 16 ]. However, the relationship between operative results in FCD undergoing MRI and Simultaneous Hybrid PET/MRI examination has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown relationships between pathologic classification and operative results undergoing MRI or PET examination with FCD [ 7 , 15 , 16 ]. However, the relationship between operative results in FCD undergoing MRI and Simultaneous Hybrid PET/MRI examination has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Toth et al in Hungry had a prospective study of MRI/PET scan on 30 nonlesional and 30 lesional cases with discordant pre-surgical results. They concluded that the results of MRI/PET scan significantly altered the original plans in 19 of 60 cases [26]. In Hong Kong, this technology has been introduced since 2017 and we have more epilepsy patients that showed promising results in pre-surgical workup (Figure 3).…”
Section: Neuro-imagingmentioning
confidence: 99%
“…FDG-PET (fluor-dezoxiglükóz pozitronemissziós tomográfia) segítségével kimutatott hipometabolikus area igen érzékenyen jelzi az epilepsziás fókuszt, ez a hipometabolizmus azonban jóval kiterjedtebb, mint az epilepsziáért ténylegesen felelős agyi terület, és csak a többi vizsgálóeljárással együtt értékelhető. Újabb vizsgálóeljárás a PET/ MRI, mely egyszerre tudja vizualizálni a morfológiai és a funkcionális eltéréseket (Tóth et al, 2021).…”
Section: Magyar Tudomány 184(2023)1unclassified